Conforming for survival: Associations between transgender visual conformity/passing and homelessness experiences. Issue 1 (2nd January 2016) - Begun, Stephanie; Kattari, Shanna K.
ABSTRACT: Transgender/gender-nonconforming (GNC) individuals face widespread discrimination and harassment, and are frequently victims of transphobic acts of violence. Furthermore, transgender/GNC individuals are twice as likely to experience homelessness as other members of the at-large population. This study uses a national survey ( N = 6, 456) to examine, specifically among transgender/GNC individuals, relationships between homelessness experiences and visual conformity/passing, and how this population's shelter-based experiences may differ based on the level to which an individual visually conforms. Results suggest that lower visual conformity/passing is positively associated with homelessness as well as negative experiences incurred while accessing shelters. Social service implications are subsequently discussed.